Chapter Sustainability in packaging design. In search of a design problem - Wszołek, Mariusz (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
In the UK, around 10 million tonnes of packaging waste is generated each year, compared to 68 million tonnes in the US. According to Eurostat, the sectors that are mainly responsible for generating packaging waste are households and services. In the article, I try to answer questions about design practices on the way to sustainability.